Ta’awun Siyasi and Winning the Election Fiqh Siyasi Perspective and Political Party Elites - Hawari, Nadirsah; Agustam, Agustam; Moh. Rosdi, Mohd. Syakir (AL-TAHRIR, 2023)
This study explains the meaning of ta’awun siyasi (political cooperation) which is usually carried out by party elites ahead of executive elections. Party elites see ta’awun siyasi not just an election rule but part of a political strategy to boost party votes during elections. In fact, there is great hope from ta’awun siyasi, but the results sometimes don’t go as desired because the impact of the coalition’s tail coat is not worth the energy expended. On the other hand, there is a communication ethic that is sometimes overlooked in addition to neglected siyasi  fiqh  norms.  The  main  problem  of  this  research  study  is how to reconcile the essential meaning of ta’awun siyasi with the ethics of coalitionalism in the style of party elites while still upholding  the  principles  of  democracy  and  siyasi  fiqh  with  the historical basis of the 2019 election coalition as a reference for the upcoming 2024 election. This study is a qualitative research that is descriptive in nature describing material objects with an analytical  knife  from  the  theory  of  democracy  and  fiqh  siyasi. The main data sources are interviews, questionnaires and other documents. The results of the study found that the true meaning of ta’awun siyasi describes sincerity and sincerity, partiality for the good  and  benefit  of  the  public  even  though  sometimes  political party elites are more entangled in purely pragmatic interests. The main principles of fiqh siyasi such as the concepts of siyasa ”˜adilah, haibah siyasasiyah, istishlah al-’ammah, siyasat al- dunya wa hirasat al-din must become a frame in building group communication.